2006
DOI: 10.1016/j.parint.2005.11.049
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of Taenia: Species definitions and origins of human parasites

Abstract: Phylogeny is fundamental as it constrains explanations about history and forms our foundation for recognizing and diagnosing species. In the absence of such a framework taxonomists historically relied on intuitive processes, personal judgment and authority, often embracing a typological view of species that disregarded otherwise unequivocal historical and biological criteria. Species of Taenia are among the most characteristic tapeworms infecting carnivores and humans as definitive hosts and indeed Taeniidae i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
95
1
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(109 citation statements)
references
References 37 publications
6
95
1
6
Order By: Relevance
“…It is intriguing and unexpected that T. madoquae, a species with a cysticercus in the skeletal muscles of a small antelope appears to be genetically closely related (of the species studied here) to T. serialis and T. multiceps, both of which have a coenurus as the larval stage. Current findings contrast with cladistic analyses by Hoberg et al [37], [38] and [39], which indicated that T. madoquae appeared in a subclade separate from both T. multiceps and T.…”
Section: Tse105) Intraspecific Variation (Bold) Highest or Lowest Vcontrasting
confidence: 99%
See 1 more Smart Citation
“…It is intriguing and unexpected that T. madoquae, a species with a cysticercus in the skeletal muscles of a small antelope appears to be genetically closely related (of the species studied here) to T. serialis and T. multiceps, both of which have a coenurus as the larval stage. Current findings contrast with cladistic analyses by Hoberg et al [37], [38] and [39], which indicated that T. madoquae appeared in a subclade separate from both T. multiceps and T.…”
Section: Tse105) Intraspecific Variation (Bold) Highest or Lowest Vcontrasting
confidence: 99%
“…This finding is similar to the cladistic study by Hoberg et al [37], [38] and [39], in which they both appeared in the same subclade. Both species have a relatively large cysticercus (usually up to 2.0-2.5 cm in the case of T. regis, and 2.5-4 cm or more for T. hydatigena) in the serosa in the coelom of the intermediate host, but they are clearly distinct based on adult morphology.…”
Section: Tse105) Intraspecific Variation (Bold) Highest or Lowest Vsupporting
confidence: 92%
“…These biogeographic scenarios are all plausible with respect to the putative timing of species splitting events (Figure 4) and they can be related to the taxon pulse theory, whereby cyclical episodes of isolation and range expansion create opportunities for a complex interplay of cospeciation, host switching and coadaptation (Hoberg andBrooks, 2008, 2010). However, they are all essentially historical narratives, which have not yet been tested empirically.…”
mentioning
confidence: 93%
“…Accurate delimitation of species provides the foundation of our knowledge of parasite life history, distribution and disease processes (Hoberg, 2006). In addition, controversy and instability in species names can have important public health implications.…”
mentioning
confidence: 99%
“…This led to the erection of the subspecies Alcataenia larina pacifica Hoberg, 1984 from the North Pacific and Alcataenia larina larina from the North Atlantic based on differences in the dimensions of cirrus sac, number of testes, as well as variations in the other morphological characters (Hoberg 1984). These putative subspecies represent independent sister-lineages that are disjunct and geographically isolated, and as such, justification may exist to elevate these to the status of separate species (Hoberg, 1984(Hoberg, , 2006Hoberg, unpublished data); that decision is beyond the scope of the current study.…”
mentioning
confidence: 99%